Penetration of 99 Richter Grapevine Roots by Phytophthora cinnamomi - Marais, P.G.; De La Harpe, A.C. (South African Journal of Enology and Viticulture, 2017)
The mechanism of penetration of 99 Richter grapevine roots by Phytophthora cinnamomi was studied by light, scanning and transmission electron microscopy. Zoospores encysted on roots within 30 min after inoculation. More spores encysted and germinated near roots than further away, indicating a response to some stimulus exuded by the roots. Germ tubes were usually not swollen at the point of entry into the roots. Penetration occurred mostly down the anticlinal walls separating epidermal cells and hyphae developed intercellularly. Swollen germ tubes were sometimes observed where intracellular hyphal growth was preceded by direct penetration of epidermal cells. Some evidence of hydrolysis of epidermal cell walls was found, whereas hydrolysis of cortical cell walls occurred more frequently. Shortly after penetration a plug of amorphous material formed in the germ tube sealing off the penetration peg within the roots. Within 48 hours after inoculation hyphae were observed in the endodermis. Invaded epidermal, cortical and endodermal cells were disrupted and underwent plasmolysis.